Implementation of lean process and its effects on library work-flow, motivation, behavior, and staff performance: a case study in one of the libraries of a Research University in Malaysia/ Mohd Fuad Haron - Haron, Mohd Fuad (Faculty of Information Management, 2022)
Lean is a philosophy of work that defines means to improve and optimize the production system, focusing on identifying and eliminating all types of waste and reducing or minimizing variability between demand and supply. It was originally developed in an auxiliary organization, but the application can be made to an entire organization as long as the overall objective remains the same, which is to increase customer appreciation while reducing waste. The practice of Lean entails constant improvement at all levels of an organization. The research aims to analyse the effect of the Lean process on library work-flow, motivation, behavior, and staff performance in one of the libraries of a research university in Malaysia. This research employs a mixed-method approach. This study will assist the university library in evaluating the implementation of the Lean process and improving the work-flow in the relevant departments. Furthermore, this will allow the library to evaluate the performance of its staff after the implementation of the Lean process. This paper explored several issues and relationships that can be further explored in future studies.